2014
DOI: 10.1161/circulationaha.113.007764
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Expectations of Long-Term Survival After the Fontan Procedure

Abstract: Background— The life expectancy of patients undergoing a Fontan procedure is unknown. Methods and Results— Follow-up of all 1006 survivors of the 1089 patients who underwent a Fontan procedure in Australia and New Zealand was obtained from a binational population-based registry including all pediatric and adult cardiac centers. There were 203 atriopulmonary connections (AP; 1975–1995), 271 lateral tunnels (1988–2006), and 532 extracardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
254
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 464 publications
(263 citation statements)
references
References 15 publications
7
254
1
1
Order By: Relevance
“…In its turn, a better Nakata index might have translated into shorter duration of the pleural drainage and shorter hospital stay after the Fontan operation in patients with APF. Furthermore, our recent study [16] demonstrated that patients staying longer in the hospital due to prolonged effusions after Fontan operation are those who would have had worse late outcomes. For those who were hospitalized for more than 18 days, the hazard of late adverse outcomes was greater.…”
Section: Commentmentioning
confidence: 98%
“…In its turn, a better Nakata index might have translated into shorter duration of the pleural drainage and shorter hospital stay after the Fontan operation in patients with APF. Furthermore, our recent study [16] demonstrated that patients staying longer in the hospital due to prolonged effusions after Fontan operation are those who would have had worse late outcomes. For those who were hospitalized for more than 18 days, the hazard of late adverse outcomes was greater.…”
Section: Commentmentioning
confidence: 98%
“…The wide spectrum of complications includes arrhythmia, ventricular dysfunction, thromboembolic events, hepatic dysfunction, and protein losing enteropathy. Nevertheless, long-term survival is good [4,5] (90% at 10 years, 83% at 20 years, and 70% to 76% at 25 years) and an increasing number of women reaching childbearing age following surgery express desire to have children. Hemodynamic changes in pregnancy are pronounced for the abnormal heart (cardiac output and stroke volume double, myocardial oxygen consumption increases by 20%, heart rate increases by 15-20%).…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has shown that anticoagulation reduces the risk in this context. Moreover, the late consequences of pregnancy on the Fontan heart need to be analyzed given the limited data on long-term survival [4,5]. Published literature includes anecdotal case reports and small series [9][10][11], which are insufficient to evaluate and identify predictors of maternal risk during pregnancy, to provide recommendations, and subsequently guide providers for counseling.…”
Section: Introductionmentioning
confidence: 99%
“…However, both lateral tunnel and extracardiac Fontan procedures have better outcomes than those with atriopulmonary connections. 22 The survival rate for patients who have the Fontan operation today is 85% at 30 years. 1 Interestingly, only between 4% and 7% of patients receive a heart transplant within 20 years of the Fontan procedure.…”
Section: Discussionmentioning
confidence: 99%